(3cJGH NhGU GdCcSjQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3EYde Cf GdCcSjQ GdCYXe dg NhGU YLjHI hbO QCjfGgG hGeJMfGg ahLOfGgG UMjMI hefgG SQjY hefgG HWF s
(3BNQgG (B:s
(3ef HOGFY CaYGd GdMLQ GdcQje GdPi jZGdH GdeGA hGdQjM JQGg ai hLg GdeGA EPG gi GdeGA efUQkG eY GdQjM JeJ GdNhGU dLGHQ Ydjg GdQMeI hGdQVhGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs